Efficacy of osimertinib and the role of sequential liquid biopsy in patients diagnosed with NSCLC harboring EGFR and BRAF mutations at baseline: insights from two case reports - Bao, Loc Carlo; Padovan, Alessia; Boscolo Bragadin, Andrea; Calvetti, Lorenzo; Guarneri, Valentina; Bonanno, Laura; Indraccolo, Stefano (Frontiers in Oncology, 2024)
Epidermal Growth Factor Receptor (EGFR) and B-Raf (BRAF) mutations are two of the most important drivers identified in non-small-cell lung cancer (NSCLC). This report highlights two cases of patients diagnosed with metastatic NSCLC bearing concurrent EGFR and BRAF mutations at baseline and treated with osimertinib as first-line treatment. Molecular profiling was conducted in the tissue and plasma at the time of initial diagnosis, and subsequent repeated liquid biopsy examinations were planned after 10 days, 28 days, and at the time of radiological progression in the frame of the prospective translational study REM. These cases suggest that osimertinib may maintain its therapeutic effectiveness even in patients presenting with a baseline BRAF co-mutation. Notably, radiological responses align with liquid biopsy observations: in both instances, follow-up liquid biopsies indicate the clearance of EGFR-mutated circulating tumor DNA (ctDNA).